The Effect of Transfer Factor Formula on Increasing Lymphocytes and Survival Rate of Koi Fish (Cyprinus carpio) Infected by Aeromonas hydrophila - Abdillah, Muhammad Robby; Lamid, Mirni; Budi, Darmawan Setia (Journal of Basic Medical Veterinary, 2022)
This study aimed to determine the effect of transfer factor on the number of fish blood lymphocytes and survival rate in koi fish infected with Aeromonas hydrophila. This Study implemented with method observation experimental with total lymphocytes and Survival rate on every treatment. Treatment shared into 4 groups namely P0 (not given Transfer factor and infected Aeromonas hydrophila), P1 (given 100 mg of transfer factor and then infected with Aeromonas hydrophila), P2 (given 200 mg of transfer factor and then infected with Aeromonas hydrophila), P3 (given 300 mg of transfer factor and then infected with Aeromonas hydrophila). Data obtained analyzed with analysis of variables (ANOVA) with using device soft SPSS 25 For Windows. Results obtained on study is Giving Transfer factors could Increase Amount Lymphocytes on Koi Fish (Cyprinus carpio). Giving Transfer factors could Increase graduation life or Survival Rate (SR) Koi Fish.Best dose on giving Transfer factor in increase total lymphocytes and increase Survival Rate (SR) on Koi fish is 200 mg.